Ergonomic Assessment Using Human Pose Estimation: A Real-Time Approach with YOLO and BlazePose - Pires, John Davi D. C.; Oliveira, Marcelo Costa; Fonseca, Baldoíno; Ribeiro, Márcio; Giglio, Bruno Antônio F.; Calzado, Alexandre Xavier (Anais Estendidos do Simpósio Brasileiro de Computação Aplicada à Saúde (SBCAS); 2025: Anais Estendidos do XXV Simpósio Brasileiro de Computação Aplicada à SaúdeDO - 10.5753/sbcas_estendido.2025.7623, 2025)
Musculoskeletal disorders (MSDs) are a major cause of workplace injuries, often linked to poor posture and repetitive movements. Traditional assessments like RULA are subjective and labor-intensive. To overcome these limitations, this study employs computer vision for automated ergonomic evaluation. Using YOLO for person detection and BlazePose for pose estimation, the system analyzes workplace postures via surveillance cameras, generating RULA scores to assess ergonomic risks. Tested on the MPI-INF-3DHP dataset, it achieves MPJPE-PA values between 243.91 mm and 295.70 mm. This scalable, objective approach enhances workplace safety. Future work will refine accuracy, handle real-world variations, and integrate real-time feedback.